2013
DOI: 10.1002/pssb.201349060
|View full text |Cite
|
Sign up to set email alerts
|

Modification of band gap in lithium niobate caused by indium incorporation

Abstract: Phone: þ52 01 953 5320214, ext: 290, Fax: þ52 01 953 5320399Measurements on transition energies near the optical absorption band edge for lithium niobate samples doped with indium at several concentrations are presented. Indirect and direct optical absorption processes were analyzed. It was found that the energies for these transitions are larger than those corresponding to undoped lithium niobate, suggesting that the energy band structure was modified by the presence of indium. For an indium concentration bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…However, DFT calculations indicated that the indirect band gaps for para- and ferroelectric lithium niobate are predicted to be at around 2.52–2.57 and 3.48–3.61 eV, respectively. , Moreover, a comparison of our results with DFT theoretical ones indicates that our samples have a band-gap value closer to the ferroelectric phase than to the paraelectric one. Experimental determinations of the lithium niobate band gap based on UV–visible spectroscopy give values ranging from 3.28 to 3.94 eV for the indirect band gap and from 3.80 to 4.12 eV for the direct band gap, respectively. ,, Hence, our values3.64 eV for the indirect band gap and from 3.97 to 4.36 eV for the direct band gapare in agreement with those previously reported.…”
Section: Resultssupporting
confidence: 91%
“…However, DFT calculations indicated that the indirect band gaps for para- and ferroelectric lithium niobate are predicted to be at around 2.52–2.57 and 3.48–3.61 eV, respectively. , Moreover, a comparison of our results with DFT theoretical ones indicates that our samples have a band-gap value closer to the ferroelectric phase than to the paraelectric one. Experimental determinations of the lithium niobate band gap based on UV–visible spectroscopy give values ranging from 3.28 to 3.94 eV for the indirect band gap and from 3.80 to 4.12 eV for the direct band gap, respectively. ,, Hence, our values3.64 eV for the indirect band gap and from 3.97 to 4.36 eV for the direct band gapare in agreement with those previously reported.…”
Section: Resultssupporting
confidence: 91%